Sistem Prioritas Proses Pengajuan Pensiun BKPSDM Lampung Tengah Menggunakan Metode Fuzzy Simple Additive Weighting (F-SAW) - I Putu Rio Kurniawan; Hariyanto Wibowo; Fitria; Chairani Fauzi (JURNAL TECNOSCIENZA, 2026)
The retirement application process at BKPSDM Lampung Tengah currently faces challenges in determining service priority due to high document volume and diverse criteria. This study aims to develop a decision support system to objectively determine retirement application priorities using the Fuzzy Simple Additive Weighting (F-SAW) method. This method was selected for its ability to handle data uncertainty through fuzzy logic and rank alternatives based on predetermined criteria weights, including retirement type, time urgency, document completeness, and number of dependents. The system was developed using the Waterfall model and implemented as a web-based application. The results demonstrate that the system produces retirement priority rankings with high accuracy. Based on functional testing using Black Box Testing, the system operates according to the design. Furthermore, validation testing shows a consistency level of 99.96% compared to manual calculations. The implementation of this system is expected to accelerate decision-making processes and enhance the efficiency of personnel administration services at BKPSDM Lampung Tengah.